2018
DOI: 10.1371/journal.pone.0191720
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA (eDNA): A tool for quantifying the abundant but elusive round goby (Neogobius melanostomus)

Abstract: Environmental DNA (eDNA) is revolutionizing biodiversity monitoring, occupancy estimates, and real-time detections of invasive species. In the Great Lakes, the round goby (Neogobius melanostomus), an invasive benthic fish from the Black Sea, has spread to encompass all five lakes and many tributaries, outcompeting or consuming native species; however, estimates of round goby abundance are confounded by behavior and habitat preference, which impact reliable methods for estimating their population. By integratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 56 publications
4
73
1
Order By: Relevance
“…At one end of the analytical spectrum is quantitative PCR (qPCR), a highly precise and sensitive way to monitor template eDNA abundance in real‐time PCR reactions (Murray, Coghlan, & Bunce, ; Taberlet et al, ). qPCR has become the standard for detection of rare species (Lacoursière‐Roussel et al, ; Nevers et al, ; Wilcox et al, ), and can provide information about species abundances based on eDNA biomass (Tillotson et al, ; Yamamoto et al, ). However, qPCR is limited in that fewer species can be studied at a time with species‐specific primers, making community‐wide abundance data more technically challenging, costly, and time consuming to ascertain (Harper et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At one end of the analytical spectrum is quantitative PCR (qPCR), a highly precise and sensitive way to monitor template eDNA abundance in real‐time PCR reactions (Murray, Coghlan, & Bunce, ; Taberlet et al, ). qPCR has become the standard for detection of rare species (Lacoursière‐Roussel et al, ; Nevers et al, ; Wilcox et al, ), and can provide information about species abundances based on eDNA biomass (Tillotson et al, ; Yamamoto et al, ). However, qPCR is limited in that fewer species can be studied at a time with species‐specific primers, making community‐wide abundance data more technically challenging, costly, and time consuming to ascertain (Harper et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Initial aquatic eDNA research was limited to determining the presence or absence of a species in freshwater ecosystems (Dejean et al, 2012;Ficetola et al, 2008;Jerde et al, 2011). Subsequently, many applications have started to emerge, including the use of eDNA to determine species abundance (Pilliod et al, 2013;Thomsen et al, 2016), biomass (Jane et al, 2015;Nevers et al, 2018;Takahara, Minamoto, Yamanaka, Doi, & Kawabata, 2012), and population structure Parsons, Everett, Dahlheim, & Park, 2018). Additionally, eDNA research has developed into sampling in the more challenging marine environment (Baker et al, 2018;Bakker et al, 2017;Foote et al, 2012;Minamoto et al, 2017;Parsons et al, 2018;Sigsgaard et al, 2016;Thomsen, Kielgast, Iversen, Møller et al, 2012;Thomsen et al, 2016;Thomsen & Willerslev, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, degree of correlation between eDNA concentration and abundance demonstrated in the field is variable between studies. A recent study of a stream‐dwelling char demonstrated a high correlation (Wilcox et al, ), but other studies reported marginally significant correlations or secondary contribution of abundance to eDNA amount (Doi et al, ; Erickson et al, ; Lacoursière‐Roussel, Côté, Leclerc, & Bernatchez, ; Klobucar, Rodgers, & Budy, ; Nevers et al, ; Pilliod, Goldberg, Arkle, Waits, & Richardson, ; Thomsen et al, ; Yamamoto et al, ). In some studies, eDNA concentration did not correlate with the biomass of the target animals (Biggs et al, ; Spear, Groves, Williams, & Waits, ).…”
Section: Introductionmentioning
confidence: 99%